2019
DOI: 10.1155/2019/7094653
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Review of Public‐Private Partnership Literature Published between 2008 and 2018

Abstract: Adopting a holistic approach in the review of the public-private partnership (PPP) literature published since 2008 by incorporating scientometric analysis and further systematic analysis, this study aims to provide the big picture of the state-of-the-art research in PPP by addressing major issues and suggesting research trends in PPP. Following a three-step research methodology, this study started from a bibliometric analysis with science mapping to provide the state-of-the-art information on PPP research keyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 131 publications
(112 reference statements)
0
27
0
2
Order By: Relevance
“…The key attributes, the best practices, as well as the barriers to PPP as to the tool for sustainable development, will offer new and interesting fields of research. Digital approaches will play a key role in sustainability‐oriented studies. Digital tools have been widely recognised as assisting decision‐making in the building industry (Ma, Li, Jin, & Ke, 2019); however, its application in PPP has rarely been examined by researchers. The potential of digital approaches, such as BIM and Mix Reality (MR), in assisting whole life design optimisation, whole life costing, integration of construction and the maintenance of assets at the early stage, should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The key attributes, the best practices, as well as the barriers to PPP as to the tool for sustainable development, will offer new and interesting fields of research. Digital approaches will play a key role in sustainability‐oriented studies. Digital tools have been widely recognised as assisting decision‐making in the building industry (Ma, Li, Jin, & Ke, 2019); however, its application in PPP has rarely been examined by researchers. The potential of digital approaches, such as BIM and Mix Reality (MR), in assisting whole life design optimisation, whole life costing, integration of construction and the maintenance of assets at the early stage, should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, VOSviewer was chosen to draw science mappings, because it is suitable for larger networks and has special text mining capabilities [22]. In construction management research, VOSviewer has been employed by more and more researchers to construct science mappings, such as public-private partnerships [23], Building information modeling [24], and building control [25]. In addition, Zhao [26] indicated that this software could also be applied to other potential research areas.…”
Section: Methodsmentioning
confidence: 99%
“…been employed by more and more researchers to construct science mappings, such as public-private partnerships [23], Building information modeling [24], and building control [25]. In addition, Zhao [26] indicated that this software could also be applied to other potential research areas.…”
Section: Co-authorship Analysismentioning
confidence: 99%
“…Public-private partnership (PPP) projects have gained worldwide popularity as an innovative method to deliver infrastructure, such as transport, water, waste, power, social and government infrastructure [1]. A public sector client initiates PPP projects with the key objective to procure public services at high quality in relation to the associated costs, and the PPP literature refers to this as Value for Money (VfM) over the project life cycle.…”
Section: Introductionmentioning
confidence: 99%